Enhancing behavioral assessment: utilizing the BASC-3 student observation system in educational settings in Qatar - Maha Al-Hendawi; Fatima Al-Maadadi; Hanadi Al-Khater; Ali Alodat; Osamah Bataineh (Springer, 2024)
Abstract Direct observation of classroom behavior in young children enriches our understanding of their behavior in its natural context, informing both assessment and intervention strategies to foster supportive learning environments. However, a notable gap in the literature concerning effective direct observation tools specifically designed for this purpose remains challenging. This observational study utilized the digital format of the The Student Observation System (BASC-3-SOS; Reynolds & Kamphaus, 2015), enabling behavior recording via smartphones, tablets, or laptops. We conducted observations for 43 young children aged four and five in classroom settings. Thirty of these children had been previously identified with behavioral problems via the Strengths and Difficulties Questionnaire (SDQ, Child Psychol Psychiatry Allied Discip. 38(5), 581-6, 1997), while 13 were considered typically developing. Each child was observed over three 20-min sessions, totaling 60 min per child. The findings revealed a significant correlation between the SDQ scores and BASC-3-SOS assessments in adaptive and maladaptive behaviors. The results indicate that young children's engagement and problem behaviors vary with teacher interactions and classroom activities. children identified with behavioral issues exhibited higher levels of maladaptive behaviors compared to their typically developing peers. The study presents the BASC-3-SOS as a promising tool for identifying general behavioral and emotional risks among young children in Qatar, suggesting its utility in enhancing early educational interventions.